SAÚDE, SANEAMENTO E PERCEPÇÃO AMBIENTAL: UMA ANÁLISE ESPACIAL DE ESTRATÉGIAS SAÚDE DA FAMÍLIA NA CIDADE DE AQUIDAUANA-MS - Renata Gehre de Oliveira Alvico (2023)
Conditions of basic sanitation contribute to improving health and reducing preventable diseases, such as infectious and parasitic diseases and, consequently, reducing hospitalization costs and mortality risks. The perception that the population has of the environment in which they are inserted is relevant information for public policy managers, as a way of seeking effective solutions to environmental problems and, above all, to the living conditions of residents. The objective of this research is to analyze the population's perception of the relationship between health and sanitation, based on the Family Health Units Bernardino Lopes, in Bairro Guanandi and Fábio Dutra dos Santos, in Vila Pinheiro, located in the city of Aquidauana, MS, in clippings spaces with different and distant basic sanitation infrastructures. The methodological contribution adopts the line of humanistic geography to meet the analysis of economic, social, environmental and perception aspects, which require the correlation of information with an emphasis on human behavior. Considers phenomenology for the analysis of health-disease perception and its relationship with sanitation. As a methodological procedure, the research was developed using a quali-quantitative approach, with the application of a structured sample interview, aimed at users of the Family Health Units, in addition to the use of data from government agencies. The results point to the user's perception of health and the correlation of sanitation with notifications of diseases such as diarrhea, dengue and leishmaniasis, which are Diseases Related to Inadequate Environmental Sanitation. Comparison of the two Family Health Units surveyed shows different socioeconomic conditions of the interviewed users, uneven distribution of basic sanitation infrastructure, especially the sewage system, and limited understanding of the relationship between health-disease and sanitation on the part of residents. Based on the results of perception and correlation of diseases related to inadequate sanitation, the research presents relevant information that can be used to improve actions and management of public health policies, to raise awareness and inform residents about the importance of basic sanitation. and its relationship with health promotion and disease prevention, through environmental health education. Keywords: Health; Basic sanitation; Environmental and health perception; Family Health Unit; Environmental health education. Keywords: health; basic sanitation; environmental and health perception; family health unit; environmental health education.